2008
DOI: 10.2298/bah0804077e
|View full text |Cite
|
Sign up to set email alerts
|

Carcass traits and meat quality of lamb fed on ration containing different levels of leucaena hay (Leucaena leucocephala L.)

Abstract: Twenty growing crossbred male lambs (¾ chios. ¼ ossimi and ½ chios. ½ ossimi) of 15.25 ± 2.00 kg initial average body weight and three months old were divided into four groups. All groups were fed on concentrate feed mixture plus 1% of live body weight wheat straw for 169 days. Four levels (zero, 200g, 400g and 600g) of leucaena hay were used. Final weight and carcass traits were evaluated. Color (L, a, b), proximate composition, pH, acidity, expressible water, water holding capacity, cooking loss, amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
4
4
1
Order By: Relevance
“…However, the values as obtained for mutton was similar to those reported by Abd El-aal and Suliman (2007) who found that the average pH-value of lamb fed on ration containing different levels of leucena leaves to be similar to those observed in this study. The low values of pH as observed in the study may be attributed to high lactic acid content in the muscle which can be a fall out of several factors, like poor pre-slaughter handling and which sometimes leads to spread of infection during transportation and in overcrowded lair ages, as well as to loss of weight, long distance travelled by the animal just prior to slaughter and also inadequate rest between the travelling and slaughtering period, absence of stunning facilities in the slaughter houses (Amha, 2006;Daniel, 2008;Elias et al, 2007;Gary et al, 2004;Yacob, 2002).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the values as obtained for mutton was similar to those reported by Abd El-aal and Suliman (2007) who found that the average pH-value of lamb fed on ration containing different levels of leucena leaves to be similar to those observed in this study. The low values of pH as observed in the study may be attributed to high lactic acid content in the muscle which can be a fall out of several factors, like poor pre-slaughter handling and which sometimes leads to spread of infection during transportation and in overcrowded lair ages, as well as to loss of weight, long distance travelled by the animal just prior to slaughter and also inadequate rest between the travelling and slaughtering period, absence of stunning facilities in the slaughter houses (Amha, 2006;Daniel, 2008;Elias et al, 2007;Gary et al, 2004;Yacob, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…But it was higher than that of cook loss value reported by Adam et al (2010). Similarly, the cook loss value for mutton as observed in this study was lower than the values reported by Abd El-aal and Suliman (2007). The differences as observed in this study may be attributed to the sex, breed, age besides both ant mortem and postmortem of animals and the carcass (Amha, 2007).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The similar appearance of different breeds in the same environment, and dissimilarity between them in different environment implies that the environment (primarily nutrition) represents dominant effect in this compound factor. Results of our study pertaining to the mineral composition of the meat partially go in line with those of Migu elez et al (2008) and Mio c et al (2009) while considerably differ from those obtained on carcases of fattened lambs that were slaughtered with >40 kg of body weight (Hoffman et al 2003;El-aal and Suliman 2008). As it has been seen from the results, the meat of Cres origin had more intramuscular fat than meat of other two origins which was also accompanied with a lower concentration of almost all the examined minerals.…”
Section: Discussionsupporting
confidence: 82%
“…Its quality is influenced by several factors including breed, sex, slaughter weight, feed types and level of feeds, age, preslaughter stress, processing and post-mortem ageing (Tejeda et al, 2008;Abd El-Aal and Suliman, 2008). Many studies have been carried out in determining lamb characteristics, but no research endeavours have been reported on quality evaluation of lamb meat by hyperspectral imaging.…”
Section: Introductionmentioning
confidence: 99%